Expression of segment a of infectious bursal disease virus in pichia pastoris - Ghazali, Mohd. Shahrin; Ahmad Raus, Raha; Amin, Noriha M.; Shohaimi, Syamsiah A.; Abu Bakar, Farah D.; Zainuddin, Norafiza; Jimat, Dzun Noraini; Nor Muhammad, Nor Azlin Alia (Journal of Pure and Applied Microbiology, 2014)
Recombinant plasmid containing segment A open reading frame 2 (ORF2) gene of infectious bursal disease virus (IBDV) of a very virulent subtype from local outbreak (strain 3529/92) was constructed. The gene encoding the IBDV structural polyprotein (N-VP2-VP3-VP4-C) was inserted into an expression vector, pPICZ prior to its transformation into Pichia pastoris by electroporation. After the induction of P. pastoris transformant with 0.5% methanol, the production of IBDV polyprotein was observed using Western blot. In P. pastoris, co- or post-translational processing of the large polyprotein occurred, generating a stable C-terminal product (VP3) of correct size, but without any detectable N-terminal product (VP2). The failure to observe the VP2 protein in Western blot analysis was probably due to the conformational epitope problem.